1989
DOI: 10.1007/bf01320636
|View full text |Cite
|
Sign up to set email alerts
|

Potential drops due to an attached bubble on a gas-evolving electrode

Abstract: It is shown how the various components of the overpotential due to an attached bubble on an electrode can be separated and estimated. By considering the resistance increments due to the presence on the electrode surface of a bubble, obtained from impedance measurements, it is possible to determine the predominant potential distribution which controls the gas evolution. A relationship between the measured overpotential and the diameter of the bubble is established. The time evolution of the overpotential due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 17 publications
3
78
1
Order By: Relevance
“…1. The steep potential jumps are related to the detachment of bubbles from the electrode, whereas the linear potential increase is due to the bubble growth, as shown in [9] from a theoretical calculation when there are a few bubbles on the electrode and when their growth is controlled by dissolved molecular gas diffusion. We must insist upon the fact that this linear potential increase is due to the growth of all the bubbles on the electrode, i.e.…”
Section: Model and Parameter Calculationmentioning
confidence: 96%
See 2 more Smart Citations
“…1. The steep potential jumps are related to the detachment of bubbles from the electrode, whereas the linear potential increase is due to the bubble growth, as shown in [9] from a theoretical calculation when there are a few bubbles on the electrode and when their growth is controlled by dissolved molecular gas diffusion. We must insist upon the fact that this linear potential increase is due to the growth of all the bubbles on the electrode, i.e.…”
Section: Model and Parameter Calculationmentioning
confidence: 96%
“…In a previous paper [9] it has been shown that under current control the overpotential fluctuations, Aqohm and At/a, can be written in terms of resistance fluctuations At/ohm(t ) -----ARe(t)I (5) At/,(t) ---ARp(t)I (6) where Iis the electrolysis current and ARe and Agp are the fluctuating parts of the electrolyte resistance, Re, and the polarization resistance (low frequency limit of the impedance), Rp, which reduces to the charge transfer resistance R t when the reaction mechanism of dissolved molecular gas production is a simple charge transfer reaction. The impedance variation induced by the presence on the electrode surface of an insulating sphere simulating a bubble has been measured for an iron disk electrode in sulphuric acid close to the corrosion potential.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…As presented by (Gabrielli et al,1989), the first correspond the transient step or the bubble´s radius variation with time and its depend of the electrolyte density. During the bubble growth the second step can be limited by diffusion of the dissolved molecular gas in the solution or by the kinetics of the production of the gas.…”
Section: The Gas Evolution Mechanismmentioning
confidence: 99%
“…Most studies have hitherto focused on mini-or micrometer sized bubbles, which are formed at and subsequently detach from the electrodes; see [20][21][22][23][24][25] and references therein. The formation of hydrogen microbubbles on a negative electrode has been witnessed by phase-contrast (a) 300 µm Figure 5.1: Phase-contrast microradiograph revealing the generation of micrometer sized hydrogen bubbles on an electrode that acts as cathode.…”
Section: Introductionmentioning
confidence: 99%